Glutathione (GSH) Production as Protective Adaptation Against Light Regime Radiation of Symbiodinium Natural Population - Moh Muhaemin; Dedi Soedharma; Hawis H Madduppa; Neviaty Putri Zamani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
Glutathione (GSH), as a wide range of low molecular weight, which found in marine microalgae and event bacteria, are essential to prevent photooxidation and productivity loss from these Radical Oxigen Species (ROS). Symbiodinium, endo-symbiont of corals, were exposed with different UV radiation combined with irradiance treatments to explore biomass specific initial response. Intracellular glutahione was observed as potential adaptive response of Symbiodinium population under environmental specific stress. The result showed that GSH production increased significantly with increasing irradiance and/or UV levels. GSH concentration was fluctuated among populations exposed by different irradiance treatments, but not effected by UV and irradiance exposure. GSH production as a response of UV exposure was higher than irradiance treatments. Both these high correlative fluctuation of intracellular GSH production and the presence of both treatments indicated protective specific adaptation of Symbiodinium under specific environmental stress, respectively. Keywords: zooxanthellae, irradiance, glutathione (GSH), corals, Fungia